Socioenvironmental influences of the sustainable management of Cascavel river watershed (Research, Society and Development, 2021)
The city of Cascavel-PR has shown, over the years, an accelerated population growth in the urban area, thus increasing environmental problems and exposing the deficiencies in public policies for basic sanitation and the environment. In order to minimize the environmental impacts of these areas, a correct management of the watershed is necessary. The objective of this study was the analysis of how population growth in the watershed region has impacted its disposition as an integral part of the environment and the society within its limits. Through that, establishing quantitative and qualitative parameters of the different aspects of the watershed and its impacts within the city. In order to verify these characteristics, two different analyses were used, relating the morphometric characteristics of the Cascavel river’s watershed, with the data of the Secretaria de Planejamento e Urbanismo - SEPLAN. The city population, according to the last Census, was around 286.172 inhabitants. The sewage service attends about 83% of the population and the pavement with asphalt in the roads reaches close to 93%. However, although public policies have improved the quality of life of the population, there was a lack of maintenance and a significant amount of siltation near the municipal lake. This region is critical for the watershed because it is its source and the presence of impacts of this order may not only affect the watershed, but also damage the sustainable development of society and the environment during the next years.